Cyclodextrin‐Cross‐Linked Hydrogels for Adsorption and Photodegradation of Cationic Dyes in Aqueous Solution. Issue 16 (9th July 2021) - Zhang, Wei; Zhang, Ying‐Ming; Liu, Yu
Abstract: Possessing three‐dimensional porous structures and tunable mechanical strengths, cyclodextrin‐containing polymeric hydrogels are one of the most promising water‐based adsorbent materials due to their easy availability, simple chemical modification and environmental friendliness. In this work, two kinds of hydrogels were prepared via the copolymerization with acrylic acid and vinyl‐derivatized β‐cyclodextrins in water. These two gels have showed good adsorption performance towards cationic dyes through the noncovalent interactions with their anionic backbones and porous network. Meanwhile, pseudo‐second‐order model was selected to clarify the adsorption kinetics process. Moreover, nano‐scaled TiO2 was doped into these resultant cyclodextrins‐based hydrogels to achieve efficient degradation of dyes upon light irradiation. The obtained TiO2 ‐loaded hydrogels could exhibit improved adsorption performance and make the adsorbed dyes photo‐degraded with the decolorization rates above 95%. It can be envisioned that such cyclodextrin‐based soft materials may find applications in dye clearance and water treatment. Abstract : Two kinds of hydrogels are prepared by the in‐situ free‐radical copolymerization of acrylic acid with vinyl‐terminated β‐cyclodextrin. Benefitting from a high porosity and abundant carboxyl groups, cationic dyes can be efficiently adsorbed onto the obtained hydrogels. Significantly, the trapped dyes can be photo‐degraded by TiO2 nanoparticles as photocatalysts in the hydrogel matrix, thus showing potential as powerful adsorbents for the removal of pollutants in water.